Comparative study between excision with primary closure versus Limberg flap for treatment of primary sacrococcygeal pilonidal sinus - Abdelraheem, Omar; Khalil, Magdy (International Surgery Journal, 2017)
Background: Surgical treatment of sacrococcygeal pilonidal sinus is associated with significant recurrence rate. However; recent study suggested the use of rhomboid excision and Limberg flap repair as feasible procedure for treatment of pilonidal sinus disease. Our aim is to evaluate the role of rhomboid excision of the pilonidal sinus with Limberg flap by comparing this procedure with the traditional excision and primary closure. Methods: This prospective study included 60 patients with sacrococcygeal pilonidal sinus. The patients were randomly divided into 2 equal groups. Rhomboid excision of the sinus with limberg flap was performed in 30 patients (group A), and excision of the sinus with primary closure was done to the other 30 cases (group B). Demographic data and surgical outcome were compared between both groups. Results: Group A showed significant early retained to work and significant less postoperative pain than group B (P=0.04 and P=0.02 respectively). Incidence of wound dehiscence, postoperative hematoma and seroma was less among group A but without significant difference. The incidence of postoperative infection and recurrence rate was significantly less in group A than group B (P=0.04 and P= 0.035 respectively). Conclusions: Rhomboid excision and Limberg flap repair is an advantageous and effective modality than simple excision with primary closure in treatment of sacrococcygeal disease. In addition, it is safe and easily procedure; it may be an ideal treatment option in management of pilonidal sinus.